Kajian Sistem Manajemen Pengelolaan Daerah Aliran Sungai Dalam Upaya Pelestarian Sumber Daya Air (Studi Kasus: Das Bone Provinsi Gorontalo) - Polie, Reynaldo Jeffry; Rispiningtati, Rispiningtati; Dermawan, Very (Fakultas Teknik, Universitas Brawijaya, 2014)
The potential of water resources Bone is the source of life for the people of Gorontalo, especially as a source of water, supply fresh water for the people of Bone Bolango. Generally in upstream of watershed use less water than the water right of it downstream, and the areas generally utilize water higher than the water use right. Excess use of water in downdstream will take from the remaining water rights of upstream. Because of these problems, it is necessary to study type of management system in related with conditions of watershed. System of incentives / disincentives is a form of integrated watershed management. The purpose of this study are to investigate the discharge quantity is used by the stakeholders, determine the required operational discharge in conservation the watershed, and establish the policy in watershed management with a system of incentives / disincentives.Keywords: Water Right, Incentives, Disincentives